(untitled) (Canadian Journal of Native Studies, 2026)
Most knowledge about the Raven’s Nest People has tended to be predominantly speculative. To address this situation, this paper proposes a hypothesis that although still speculative, presents a probable explanation, even a compelling one, about the ancestral origins of the Raven’s Nest Indigenous People. Further research and the gathering of stories including the oral history of the Raven’s Nest People will still have to be sought, from Elders of the Crow Nation, and other Indigenous tribes that frequented the region of the Crowsnest Pass, however, it is hoped that this paper will provide the necessary foundation to advance further research. The paper will conclude with a summary of the research and theories about the demise of both the Ktunáxa and the Raven’s Nest Peoples.